The effects of honey processing on nanoparticles in Astragali Radix decoction: Self-assembly, bioavailability, and bioactivity - Zhang, Weiye; Song, Jinjing; Su, Xiao; Zhu, Dandan; Xu, Yan; Jia, Xiaobin; Feng, Liang; Yang, Bing (Food research international, 2025)
Compared with Astragali Radix (AR), honey-processed Astragali Radix (HAR) exhibits superior efficacy in both Qi-tonifying (enhancement of the body's vital energy to increase fatigue resistance, improve nutrient absorption, and strengthen defenses against illnesses) and immunomodulatory activity. While existing researches have predominantly attributed HAR's enhanced bioactivity to quantitative changes in chemical constituents, this study focused on the material basis of decoction efficacy (nanoparticles), and investigated the effects of honey processing on the physicochemical properties, chemical composition, self-assembly, bioavailability, and bioactivity of these nanoparticles. Our findings revealed that both AR decoction-derived nanoparticles (ARD-NP) and HAR decoction-derived nanoparticles (HARD-NP) were primarily formed through the self-assembly of polysaccharides, protein, and small molecules via hydrogen bonding and hydrophobic interactions. In comparison to ARD-NP, HARD-NP contained higher concentrations of polysaccharides and flavonoids, while demonstrating smaller particle size, narrower size distribution, and superior structural stability. Notably, honey processing significantly improved the intestinal absorption and oral bioavailability of four representative flavonoids (CAG, ON, CA and FMN) in the nanoparticles, leading to enhanced bioactivity in Qi-tonifying. This study innovatively focuses on the nanoparticles commonly found in decoctions as the subject of investigation, providing a new perspective on the mechanisms underlying the enhanced efficacy of HAR. Furthermore, it provides scientific references for the processing of medicine food homology plants, as well as the development of novel functional foods. Separation and characterization of nanoparticles from Astragali Radix and honey-processed Astragali Radix decoctions, and the effects of honey processing on the self-assembly, bioavailability, and bioactivity of nanoparticles. [Display omitted] •ARD-NP and HARD-NP were successfully isolated and characterized.•Polysaccharides were isolated from ARD-NP and HARD-NP for chemical characterization and conformational analysis.•Self-assembly mechanism of ARD-NP and HARD-NP was analyzed.•The effects of honey processing on the self-assembly, bioavailability, and bioactivity of nanoparticles were investigated.